1996
DOI: 10.1007/bf02093601
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human colonic cell line proliferation and phenotype by sodium butyrate

Abstract: Colonic butyrate may maintain mucosal differentiation and oppose carcinogenesis. We characterized butyrate effects on differentiation, proliferation, and matrix interactions in Caco-2 and SW620 human colonic cells. Differentiation was assessed by brush border enzyme activity and doubling time by serial cell counts. Motility across matrix proteins was quantitated by monolayer expansion and correlated with adhesiveness to matrix. Integrin subunit surface pools were measured by immunoprecipitation. Butyrate-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…APC is able to increase MDA-MB-231 cell migration over Na butyrate treatment alone by the same ratio as APC treatment compared to control. Further, the pathways activated by Na butyrate [52,53] are not the same pathways utilized by APC to increase migration in these cells. Other pathways, such as MAPK and PI3K pathways [26], that have been implicated in the mechanism by which APC increase HUVEC proliferation may have a role in increasing migration in the MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…APC is able to increase MDA-MB-231 cell migration over Na butyrate treatment alone by the same ratio as APC treatment compared to control. Further, the pathways activated by Na butyrate [52,53] are not the same pathways utilized by APC to increase migration in these cells. Other pathways, such as MAPK and PI3K pathways [26], that have been implicated in the mechanism by which APC increase HUVEC proliferation may have a role in increasing migration in the MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 90%
“…Na butyrate inhibits histone deacetylase, increases p21 expression, and decreases cyclin D gene expression [50] resulting in an arrest of the cell in G2 [51]. Na butyrate also induces cell differentiation [50], as shown with an increase in lipid accumulation, and a reduction in migration across multiple extracellular matrices [52]. We found that unlike the effects of APC on HUVEC proliferation, in breast cancer cells, binding to EPCR and activation of PAR-1 by APC increase migration but not proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…IAP is a well-established marker of di erentiation in HT29 cells and other colon cancer cell lines (Choi et al, 1990;Hodin et al, 1996, Schroy et al, 1994Goldberg et al, 1996;Navarro et al, 1997;Basson et al, 1996). IAP activity was examined using a histochemical demonstration kit for alkaline phosphatase detection (Sigma) (Goldberg et al, 1996) and also by Western blot analysis using a rabbit polyclonal antibody that recognizes human intestinal alkaline phosphatase (Dako), as described previously (Goldberg et al, 1996).…”
Section: E Ect Of P27 Kip1 Overexpression On Cell DI Erentiationmentioning
confidence: 99%
“…Sodium butyrate (SB) was used for induction of di erentiation. This short chain fatty acid is a di erentiating agent for various cell types (Navarro et al, 1997;Siavoshian et al, 1997;Basson et al, 1996;Conway et al, 1995;Swarovsky et al, 1994). By histochemical analyses IAP positive cells were only rarely detected in the untreated vector control and the overexpressor derivatives.…”
Section: E Ect Of P27 Kip1 Overexpression On Cell DI Erentiationmentioning
confidence: 99%
“…SCFAs are well known to promote differentiation in transformed erythroid and colonic epithelial cell lines, [26][27][28][29] but their effects on erythroid differentiation in primary cells had not been described. Normal erythroid differentiation in murine development parallels advancing fetal age.…”
Section: Introductionmentioning
confidence: 99%